2007
DOI: 10.1016/j.neuro.2007.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of HIV-1 Tat protein: Involvement of D1 dopamine receptor☆

Abstract: Neurotoxic viral proteins released from HIV-infected cells are believed to play a major role in the pathogenesis of the dementia displayed in a significant number of AIDS patients. HIV-1 associated neuropathology severely affects dopaminergic regions of the brain. Growing evidence indicates that HIV-1 neurotoxic proteins, such as Tat may affect the function of the dopamine transmission system. In turn, molecular components of dopamine neurotransmission may participate in a complex network of Tat-induced cell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 47 publications
2
49
0
Order By: Relevance
“…Thus, it is plausible that cumulative oxidative stress generated by HIV proteins and dopamine metabolism may potentiate severity and accelerate progression of HAND/HAD. It is interesting to note that dopamine receptor-1 is involved in Tat-induced neurotoxicity [77] where oxidative stress may play a contributory role.…”
Section: Dopamine Hiv and Oxidative Stressmentioning
confidence: 99%
“…Thus, it is plausible that cumulative oxidative stress generated by HIV proteins and dopamine metabolism may potentiate severity and accelerate progression of HAND/HAD. It is interesting to note that dopamine receptor-1 is involved in Tat-induced neurotoxicity [77] where oxidative stress may play a contributory role.…”
Section: Dopamine Hiv and Oxidative Stressmentioning
confidence: 99%
“…Complete review of glutamatergic NMDAR exceeds the purpose of the review (see King et al, 2006). Nevertheless, Tat/NMDAR mediated toxicity likely effects DA systems; and research in our laboratory (Silvers et al, 2007) has recently demonstrated a D1 receptor/Tat interaction, whereby Tat-induced neurotoxicity to rat fetal midbrain cell cultures was abrogated by a D1 receptor antagonist (SCH23390) where D1 receptor binding was abundant. Interestingly, this study demonstrated a lack of SCH23390-mediated attenuation of Tat-induced neurotoxicity to fetal hippocampal culture, where D1 receptor binding is low.…”
Section: Hiv Infection-oxidative Stress Is the Alteration And Damage mentioning
confidence: 99%
“…Interestingly, this study demonstrated a lack of SCH23390-mediated attenuation of Tat-induced neurotoxicity to fetal hippocampal culture, where D1 receptor binding is low. The correlation between D1 receptor binding and SCH23390 protection from Tat-toxicity demonstrates a possible role for D1 receptors in the neurotoxic mechanism of Tat (Silvers et al, 2007). Furthermore, based on evidence for NMDAR/D1 regulatory and structural heteromeric interactions (Cepeda and Levine, 2006;Missale et al, 2006), Silvers et al (in press) speculate a possible NMDAR/D1 reciprocal regulation of pro-apoptotic cascades, mediated by Tat and/or Tat-induced ROS.…”
Section: Hiv Infection-oxidative Stress Is the Alteration And Damage mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Tat was shown to increase the potassium-evoked outflow of DA early (2 hours) after the injection into rat nucleus accumbens (Ferris et al, 2007). The protective action of the D1 receptor selective antagonist, SCH 23390, against Tat and Tat+cocaine in vitro , Silvers et al, 2007 suggested that concurrent changes in DA homeostasis induced by Tat and cocaine may contribute to their combined toxicity.…”
Section: Discussionmentioning
confidence: 99%